Bead based facile assay for sensitive quantification of native state green fluorescent protein. Issue 22 (1st April 2020) - Kim, Jung Min; Seong, Baik Lin; Lim, Dong-Kwon
Abstract : A facile method for the quantification of native state protein is strongly required to accurately determine the amount of expressed protein of interest. Abstract : A facile method for the quantification of native state protein is strongly required to accurately determine the amount of expressed protein of interest. Here we report a simple bead-based assay, which can sensitively quantify the amount of native state green fluorescent protein using Ni-NTA (nickel-nitrilotriacetic acid)-modified microbead particles. The bead-based method is simple and straightforward to perform and it showed a highly sensitive capability to detect the expressed fluorescent protein because of the enriched fluorescent protein on the beads.